2011
DOI: 10.1128/jcm.02243-10
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Rapid MGIT TBc Identification Test for Culture Confirmation of Mycobacterium tuberculosis Complex Strain Detection

Abstract: A culture confirmation test for the detection of Mycobacterium tuberculosis complex strains that uses a lateral-flow immunochromatographic assay to detect the MPB64 antigen, the MGIT TBc identification (TBc ID) test, has been developed. We evaluated the performance of the TBc ID test in the detection of the M. tuberculosis complex in 222 primary-positive liquid cultures. We compared these results to those of nucleic acid-based identification and conventional biochemical tests. The validity of the TBc ID test w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 19 publications
0
37
0
1
Order By: Relevance
“…Meta-analyses of the data, including data from the current study, demonstrated high sensitivity and specificity for all 3 tests, with high positive and negative predictive values for clinical isolates tested (Table 3). There was no evidence that sensitivities and specificities differed between tests even when we confined the meta-analysis to studies that used 16S rRNA sequencing or two or more independent, validated reference methods (4, 12, 16-18 (4)(5)(6)33). The mpb64 gene was sequenced for 27 of 53 (51%) clinically independent isolates for which the MPT64 ICT gave a false-negative result, and a mutation was demonstrated in 23 (85%) of those 27 isolates (12,16,17,20,22,33 Our data and meta-analysis demonstrate noninferiority of MGIT TBcID to LPA for MTBC detection and similar high sensitivities and specificities of 3 commercial MPT64 assays across a range of geographical locations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Meta-analyses of the data, including data from the current study, demonstrated high sensitivity and specificity for all 3 tests, with high positive and negative predictive values for clinical isolates tested (Table 3). There was no evidence that sensitivities and specificities differed between tests even when we confined the meta-analysis to studies that used 16S rRNA sequencing or two or more independent, validated reference methods (4, 12, 16-18 (4)(5)(6)33). The mpb64 gene was sequenced for 27 of 53 (51%) clinically independent isolates for which the MPT64 ICT gave a false-negative result, and a mutation was demonstrated in 23 (85%) of those 27 isolates (12,16,17,20,22,33 Our data and meta-analysis demonstrate noninferiority of MGIT TBcID to LPA for MTBC detection and similar high sensitivities and specificities of 3 commercial MPT64 assays across a range of geographical locations.…”
mentioning
confidence: 99%
“…There was no evidence that sensitivities and specificities differed between tests even when we confined the meta-analysis to studies that used 16S rRNA sequencing or two or more independent, validated reference methods (4, 12, 16-18 (4)(5)(6)33). The mpb64 gene was sequenced for 27 of 53 (51%) clinically independent isolates for which the MPT64 ICT gave a false-negative result, and a mutation was demonstrated in 23 (85%) of those 27 isolates (12,16,17,20,22,33 Our data and meta-analysis demonstrate noninferiority of MGIT TBcID to LPA for MTBC detection and similar high sensitivities and specificities of 3 commercial MPT64 assays across a range of geographical locations. A small minority of MTBC isolates are not detected by MPT64 assays due to deletion or mutation of the mpb64 gene (absent from some M. bovis BCG strains) (1,12,16,17,20,22,33) or to low MPT64 concentrations in early cultures (10,18) or mixed cultures (10,18).…”
mentioning
confidence: 99%
“…Both molecular methods demonstrated 100% agreement, identifying 84 isolates as M. tuberculosis isolates and 41 isolates as non-MTC isolates. The results of TBc ID (with a reported specificity and sensitivity of 92.4 to 100% and 94.9 to 100%, respectively [18,25,29]) and the molecular methods were concordant for 79 MTC isolates and 37 non-MTC isolates. The ssrA genes of the 9 discordant samples were sequenced to consolidate results.…”
Section: Resultsmentioning
confidence: 87%
“…These tests are rapid requiring only minutes to perform after growth of the organism but literature reports indicate variable performance (Martin et al, 2011;Said et al, 2011;Steingart et al, 2011;Yu et al, 2011) 6. Direct identification of M. tuberculosis from clinical specimens…”
Section: Immunoassay Methodsmentioning
confidence: 99%